A Systematic Review: Covid-19 and Expansion of PESTLE Framework: Time to Perceive Health Environment As a Separate Dimension - VIVEK, Ramakrishnan (International Journal of Environmental, Sustainability, and Social Science, 2024)
The article explores the impact of the COVID-19 pandemic on the global economy, utilising macroeconomic concepts. Further, how organisations worldwide can use the strategic management technique of drawing up a PESTLE analysis to provide focused attention to each factor and macroeconomic party, which ultimately comprises the entire economy, with special attention being focused on the expansion of the environmental factor. The study sought to determine whether healthcare should be considered as a separate dimension under the environmental category in a PESTLE analysis as seen by the effects of the current pandemic and, if so, what the arguments in favour and against were. The methodology was used to gather data from online journals relating to the relevant healthcare ministries, and a comprehensive review was conducted based on existing sources. The scenarios unfolded as the pandemic first broke out, the policies imposed by governments and shortcomings as policymakers were discussed, and the current policies utilised to ensure the brunt of the pandemic did boomerang again were analysed. This research article concludes with the results of the COVID-19 pandemic; healthcare can be considered a separate dimension of the environmental factor in PESTLE analysis, which directly influences the macroeconomy.